2004
DOI: 10.1562/fr-03-15.1
|View full text |Cite
|
Sign up to set email alerts
|

A Far-red Fluorescent Contrast Agent to Image Epidermal Growth Factor Receptor Expression

Abstract: Recent developments in optical technologies have the potential to improve the speed and accuracy of screening and diagnosis of curable precancerous lesions and early cancer, thereby decreasing the costs of detection and management of epithelial malignancies. The development of molecular-specific contrast agents for markers of early neoplastic transformation could improve the detection and molecular characterization of premalignant lesions. In the oral cavity, epidermal growth factor receptor (EGFR) overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…Imaging depth could be increased by integrating longer wavelength laser lines, e.g. near infrared [25], or by using non-linear imaging techniques, such as two-photon microscopy [26], for excitation of fluorophores well below the liver surface. This would potentially also ameliorate diagnosis of tissue fibrosis, which in the present study has only been observed at the liver surface and was therefore not quantified.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging depth could be increased by integrating longer wavelength laser lines, e.g. near infrared [25], or by using non-linear imaging techniques, such as two-photon microscopy [26], for excitation of fluorophores well below the liver surface. This would potentially also ameliorate diagnosis of tissue fibrosis, which in the present study has only been observed at the liver surface and was therefore not quantified.…”
Section: Discussionmentioning
confidence: 99%
“…Hav− ing established the feasibility of in−vivo molecular imaging in ro− dents in the present study, it is, however, tempting to speculate that translation of these findings into flexible endomicroscopy will soon offer the possibility of molecular imaging in humans in real time during endoscopy. Furthermore, exploitation of al− ternate laser lines and detection bands to achieve deeper tissue imaging [18] and co−localization of multiple fluorophores (mul− tichannel imaging) will extend the number of molecular biologi− cal and microarchitectural features that can be investigated in organs and cells in their natural environment. In−vivo confocal imaging with this new handheld probe could therefore contrib− ute to a deeper understanding of microarchitecture and cellular function and interactions in human diseases such as cancer and inflammation.…”
Section: Molecular Imaging Of Somatostatin Receptor−positive Cells Inmentioning
confidence: 99%
“…In the future, however, imaging depth will be increased by integrating longer wavelength laser lines, e.g. near infrared, or using nonlinear imaging techniques such as two-photon microscopy (31,32). In analogy to pancreatic islet cells, confocal laser scan microscopy allowed visualization of sstr in tubular cells of the renal FIG.…”
Section: Discussionmentioning
confidence: 99%